Pineal parenchymal tumors: Case series - Mohiuddin KM; Sailaja M; Rao SI; Panigrahi MK; Reddy KA; Naidu CS (Journal of Medical and Scientific Research, 2016)
Background: Pineal parenchymal tumors (PPTs) are uncommon tumors comprising of pineocytoma (PC), pineal parenchymal tumor of intermediate differentiation (PPTID) and pineoblastoma (PB). Morphological sub typing and histological grading based on mitotic index and neurofilament (NF) immunostaining are the factors affecting the survival of these patients. Treatment strategy and prognosis of PPTIDs remain controversial with limited data available on pathologic features and biologic behavior of PPTID.